Modulating lipid metabolism improves tumor immunotherapy - Yi Zhang; Yu Ping; Qiuqing Fan (Journal for ImmunoTherapy of Cancer)
Immunotherapy has progressed significantly in cancer treatment; however, several factors influence its outcomes. Abnormal lipid metabolism, which is frequently observed in cancers, promotes tumor proliferation, invasion, and metastasis. Li et al from the Medical Oncology Department of Chongqing University Cancer Hospital constructed a lipid metabolism scoring system and reported that MK1775 inhibited fatty acid oxidation in tumor-associated macrophages and reduced T-cell infiltration, further enhancing the efficacy of immunotherapy. This study demonstrated the critical role of lipid metabolism scoring system and lipid metabolism in immunotherapy. Currently, the metabolism of lipids, such as fatty acids, phospholipids, and cholesterol, has been reported to affect the tumor microenvironment by regulating immune cells, including T cells, natural killer cells, and macrophages. These metabolic changes can impair the efficacy of immunotherapy, resulting in tumor progression. Consequently, lipid metabolism emerges as an important immune regulator for improving immunotherapeutic outcomes and provides a novel and powerful strategy for tumor combination therapy.